Giáo trình vật lý lượng tử: tóm tắt lý thuyết và bài tập (Giáo dục, 2017)
Part I The Special theory of relativity - Part II The quantum theory of electromagnetic radiation and matter - Part III Hydrogenlike atoms - Part IV Many-electron atoms - Part V Nuclear physics - Part VI Atomic systems